1996
DOI: 10.1597/1545-1569_1996_033_0213_protlv_2.3.co_2
|View full text |Cite
|
Sign up to set email alerts
|

Proprioceptive Representation of the Levator Veli Palatini Muscle in the Solitary Nucleus of the Rat

Abstract: The levator veli palatini muscle is innervated by motoneurons of the glossopharyngeal nerve, which are located within the ambiguus nucleus; however, little is known about the afferent fibers of this muscle. A horseradish peroxidase study was conducted in rats following injection into the levator veli palatini muscle branch to reveal the location and the distribution of dendrites of the afferent fibers of the muscle. Terminal labels were densely distributed in the lateral region of the solitary nucleus, which r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…There are only a few reports indicating that tongue muscles are innervated by muscle spindles (Kubota et al ., 1975; Purwar, 1979; Smith, 1989; Saigusa et al ., 2004). In contrast, several studies have demonstrated that lingual muscles and extrinsic tongue muscles lack typical muscle spindles in man and young adult Wistar rats (Bowman, 1968; Bout & Dubbeldam, 1991; Sherif et al ., 1991; Furusawa et al ., 1996). Electrophysiological studies have shown that the trigeminal sensory afferents influence and integrate tongue movement (Morimoto et al ., 1978; Lowe, 1984; Tolu et al ., 1993; Tolu et al ., 1994; Ishiwata et al ., 1997; Ishiwata et al ., 2000).…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few reports indicating that tongue muscles are innervated by muscle spindles (Kubota et al ., 1975; Purwar, 1979; Smith, 1989; Saigusa et al ., 2004). In contrast, several studies have demonstrated that lingual muscles and extrinsic tongue muscles lack typical muscle spindles in man and young adult Wistar rats (Bowman, 1968; Bout & Dubbeldam, 1991; Sherif et al ., 1991; Furusawa et al ., 1996). Electrophysiological studies have shown that the trigeminal sensory afferents influence and integrate tongue movement (Morimoto et al ., 1978; Lowe, 1984; Tolu et al ., 1993; Tolu et al ., 1994; Ishiwata et al ., 1997; Ishiwata et al ., 2000).…”
Section: Introductionmentioning
confidence: 99%